Arched Bamboo Charcoal as Interfacial Solar Steam Generation Integrative Device with Enhanced Water Purification Capacity. (29th January 2019) - Li, Zhengtong; Wang, Chengbing; Lei, Tao; Ma, Hailing; Su, Jinbu; Ling, San; Wang, Wei
Abstract: Interfacial solar steam generation (ISSG) has received increasing attention in both industry and academia, and is considered a method with great potential for wastewater treatment and desalination. These practical applications require materials that fulfil several requirements: being low cost, being scalable in terms of processing, being environmentally friendly, and having a high, stable optical–thermal conversion efficiency of solar vaporization. Currently, biomass materials show very promising prospects for ISSG systems. Here, it is observed that bamboo charcoal (BC) possesses a series of unique advantages that make it a highly efficient ISSG device. The broadband light absorption and the arched and porous structural features of BC fulfil all the basic requirements of an ISSG device in localized heating, heat management, and water supply. The self‐contained arched BC device demonstrates high evaporation efficiency (84% under 1 sun radiation) and superb stability under strongly acidic, strongly alkaline, and intense light environment conditions. More importantly, the porous BC device can provide stable fresh water production that simultaneously promotes the purification of water via evaporation by heating. Finally, the low cost, environmentally sustainable, mechanically robust, and long‐term stable BC device is a potential opportunity for wastewater treatment and desalination in underdeveloped areas. Abstract : Bamboo charcoal for daily use has been successfully applied to photothermal conversion. Its application is based on excellent optical, thermal, and stable mechanical properties rather than physical adsorption. Arched bamboo charcoal with many pores as a self‐contained solar steam generation can achieve 84% evaporation efficiency at 1 kW m −2 . Its water purification capacity is also enhanced via evaporation of local heating.